EVALUASI KINERJA DAN KEAMANAN APLIKASI WHATSAPP TERHADAP KEPERCAYAAN KONSUMEN METODE USABILITY TESTING - Pradana, Refki; Alfarisyi , Hafiz (Universitas Majalengka, 2024)
The rapid development of technology in this era has brought significant changes to various aspects of society's life, especially with the emergence of social media, which adds complexity to individual technology needs. One of the essential technologies is the WhatsApp application. WhatsApp is a cross-platform messaging application that allows message exchanges using internet data packages, similar to email, web browsing, and others. The various unique features offered by WhatsApp make it the primary medium used by university students to communicate and share information. To evaluate the performance and security of the WhatsApp application regarding consumer trust, an analysis was conducted using the usability testing method. By distributing questionnaires to university students, 50 respondents were obtained. This research aims to determine whether WhatsApp has satisfactory performance and security among university students.